TELEHEALTH TOOLS IN FIGHTING COVID-19 IN CEARÁ - Fernandes Augusto Filho, Rômulo (2022)
To reflect on how information technologies can be used, with opportunities and development of new ways of providing health care, highlighting the digital health care model and the tools used by the State Health Department of Ceará. A reflection on the Telehealth tools used by the State Health Department of Ceará, establishing analogies with the use of the main technological tools. With a focus on digital models based on Telehealth, applications, the use of websites and chatbots, the use of telescreens and teleconsultation tools are shown as a great ally of health professionals and the population served. Access, the accuracy of data, applicability, and acceptance by society contribute to the expansion of Telehealth, representing a new niche of services to be offered, ensuring continuous and comprehensive monitoring.